Sagot :
Step-by-step explanation:
6n5(5n2−7n+1)
=(6n5)(5n2+−7n+1)
=(6n5)(5n2)+(6n5)(−7n)+(6n5)(1)
=30n⅞−42n6+6n^5
7r2(3r2−2r−5)
=(7r2)(3r2+−2r+−5)
=(7r2)(3r2)+(7r2)(−2r)+(7r2)(−5)
=21r⁴−14r³−35r²
3n2(8n2+5n−8)
=(3n2)(8n2+5n+−8)
=(3n2)(8n2)+(3n2)(5n)+(3n2)(−8)
=24n⁴+15n³−24n²
3a3(8a+b)
=(3a3)(8a+b)
=(3a3)(8a)+(3a3)(b)
=24a⁴+3a³b
8xy(x+8y)
=(8xy)(x+8y)
=(8xy)(x)+(8xy)(8y)
=8x²y+64xy²
(−3v)(−8u2−8uv−7v2)
=(−3v)(−8u2+−8uv+−7v2)
=(−3v)(−8u2)+(−3v)(−8uv)+(−3v)(−7v2)
=24u²v+24uv²+21v³
(−y2)(−8x2−6xy−y2)
=(−y2)(−8x2+−6xy+−y2)
=(−y2)(−8x2)+(−y2)(−6xy)+(−y2)(−y2)
=8x²y²+6xy³+y⁴
(n−7)(3n+1)
=(n+−7)(3n+1)
=(n)(3n)+(n)(1)+(−7)(3n)+(−7)(1)
=3n2+n−21n−7
=3n²−20n−7
(7n+8)(8n−3)
=(7n+8)(8n+−3)
=(7n)(8n)+(7n)(−3)+(8)(8n)+(8)(−3)
=56n2−21n+64n−24
=56n²+43n−24
(5p−5)(7p+6)
=(5p+−5)(7p+6)
=(5p)(7p)+(5p)(6)+(−5)(7p)+(−5)(6)
=35p2+30p−35p−30
=35p²−5p−30
SANA MAKATULONG po